THE EXISTENCE OF ISLAMIC RELIGIOUS EDUCATION TEACHERS IN MAINTAINING THE QUALITY OF LEARNING - Muis, Andi Abd.; Salmiati, Salmiati; Darmi, Darmi; Muhandes, Muhandes; Kasmin, Kasmin (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research aims to provide an overview of the quality of Islamic Education learning in the minority Islamic environment of SMKN 1 North Toraja. It seeks to understand the role of Islamic Education teachers in maintaining the quality of Islamic Education learning in the minority setting of SMKN 1 North Toraja and identify the challenges faced by Islamic Education teachers in maintaining the quality of learning in the minority environment of SMKN 1 North Toraja. The research type employed is qualitative (Field Research) conducted at SMKN 1 North Toraja, utilizing a Descriptive Qualitative approach. Research instruments consist of observation guidelines, interview guidelines, and documentation guidelines. Data collection procedures encompass observation, interviews, and documentation. Data analysis techniques include data reduction, data presentation, conclusion drawing, and verification. The research findings are as follows: 1) The quality of learning at SMKN 1 North Toraja is still lacking due to Islamic Education teachers not fully adhering to the lesson plan (RPP) because students have minimal knowledge of Islam and low intellectual abilities. 2) Islamic Education teachers not only teach and guide students but also provide support, acting as motivators and administrators. Importantly, Islamic Education teachers play a role as a second parent for students within the school environment. 3) Challenges faced by Islamic Education teachers in maintaining the quality of learning include students' lack of interest in learning Islamic Education, insufficient knowledge about Islam among students, and environmental factors affecting the quality of learning, particularly in a minority context.